(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Adherence to antiretroviral (ARV) treatment plays a decisive role in controlling viral load, limiting drug resistance, and improving the effectiveness of HIV/AIDS treatment. Objective: o assess the rate of ARV treatment adherence and identify some factors related to adherence among people living with HIV/AIDS at Nga Bay Medical Center, Can Tho City, in 2025. Subjects and methods: A descriptive cross-sectional study with analytical components was conducted among people living with HIV/AIDS who were receiving ARV treatment. Results: Men accounted for 66.3%, mainly concentrated in younger age groups (especially 25–29 years old). Most patients reported good adherence to ARV treatment; among non-adherent behaviors, forgetting to take medication was the most common (12.0%). Analysis of related factors showed that family support increased the likelihood of adherence (OR = 3.1; p = 0.043), whereas working far from the local area reduced adherence (OR = 3.2; p = 0.027). Disease-related characteristics, such as route of transmission, disease stage, and opportunistic infections, were associated with treatment adherence (p < 0.05). Conclusion: The level of ARV treatment adherence at the study site was relatively good. Strengthening reminder measures, providing individualized counseling, and enhancing social support are necessary to maintain long-term adherence.